Effect of phospholipase A2 hydrolysis products on calcium oxalate precipitation at lipid interfaces - Sharbaugh, Denise M (Langmuir : the ACS journal of surfaces and colloids, 2010)
Urinary stones are commonly composed of an inorganic component, calcium oxalate, or calcium phosphate and an organic matrix of lipids, carbohydrates, and proteinaceous matter. Of interest is the role that the organic matrix elements may play as catalysts for the heterogeneous nucleation of the calcium salts, and a number of studies have examined the role of lipids in calcium oxalate monohydrate (COM) formation. In this study, products of lipid hydrolysis from phospholipase A(2) (PLA(2)) are examined for their effect on COM formation using Langmuir monolayers as model lipid membrane assemblies. The enzyme PLA(2) hydrolyzes DPPC monolayers in the presence of a supersaturated calcium oxalate subphase, inducing the rapid and plentiful nucleation of calcium oxalate at the lipid interface. To investigate the cause of increased crystal formation in the presence of the enzyme, Langmuir monolayers modeling the hydrolysis products were investigated. Calcium oxalate crystal growth at a ternary monolayer of dipalmitoylphosphatidylcholine (DPPC), palmitic acid (PA), and a 22-carbon chain lysophospholipid (22:0 Lyso PC) dramatically increases relative to monolayers of just DPPC. Binary monolayers of DPPC with either PA or the 22:0 Lyso PC and single-component monolayers of PA were also studied. It is demonstrated that the fatty acid generated during lipid hydrolysis causes a significant increase in the extent of heterogeneous nucleation of calcium oxalate from supersaturated solutions. The results imply a possible link between increased phospholipase activity, which is associated with hyperoxaluria, and calcium oxalate precipitation